Leadership in new ventures: complexity managed by teams. (27th January 2009) - Newth, Jamie; Corner, Patricia Doyle
The purpose of this paper was to investigate the extent to which leadership in new venture entrepreneurial teams was consistent with a complex systems framework. A case study design was used and qualitative evidence was collected and analysed relative to the three complexity leadership roles outlined by Uhl-Bien et al. (2007). These roles were administrative, adaptive and enabling leadership. The adaptive leadership role was most strongly reflected in the case studies, although the evidence did reveal a mix of the three roles described by Uhl-Bien et al. Examples of adaptive leadership include the development of prototype products, the creation of revenue streams from new products, entry into overseas markets, and the sale of an innovative product to the dominant firm in the industry. The collected qualitative evidence was highly consistent with the conceptual framework of Complex Adaptive Systems (CASs) particularly because new venture teams defied categorisation into the precise categories and units of analysis commonly assumed in the literature. This consistency encourages the application of complexity and chaos notions to future research on new ventures, even though the current findings are most appropriately interpreted as exploratory.